New knowledge on the demographic history of sheep - CGIAR Research Program on Livestock (2020)
Journal article on whole-genome resequencing of wild and domestic sheep. The research knowledge can be used to: guide ex-situ conservation priorities; contribute to discovery of genetic variants for economic and ecologically important traits; and feed into admixture analysis to determine an individual animal's breed composition.